2016
DOI: 10.1080/10408444.2016.1214681
|View full text |Cite|
|
Sign up to set email alerts
|

Glyphosate epidemiology expert panel review: a weight of evidence systematic review of the relationship between glyphosate exposure and non-Hodgkin’s lymphoma or multiple myeloma

Abstract: We conducted a systematic review of the epidemiologic literature for glyphosate focusing on nonHodgkin's lymphoma (NHL) and multiple myeloma (MM) -two cancers that were the focus of a recent review by an International Agency for Research on Cancer Working Group. Our approach was consistent with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews. We evaluated each relevant study according to a priori criteria for study quality: adequacy of study size, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…The epidemiology Expert Panel conducted a systematic review of the published glyphosate literature for the two cancers that were the focus of IARC's epidemiology review: nonHodgkin's lymphoma (NHL) and multiple myeloma (MM) (see Acquavella et al (2016) for additional details). Initially, an exhaustive search of the medical literature was performed to identify all epidemiological studies that examined the relationships between reported use of glyphosate and NHL or MM.…”
Section: Epidemiological Datamentioning
confidence: 99%
“…The epidemiology Expert Panel conducted a systematic review of the published glyphosate literature for the two cancers that were the focus of IARC's epidemiology review: nonHodgkin's lymphoma (NHL) and multiple myeloma (MM) (see Acquavella et al (2016) for additional details). Initially, an exhaustive search of the medical literature was performed to identify all epidemiological studies that examined the relationships between reported use of glyphosate and NHL or MM.…”
Section: Epidemiological Datamentioning
confidence: 99%
“…Among environmental factors, glyphosate or its formulated products have been indicated to be linked with increased incidence of and mortality by multiple diseases (including cataract related to subsequent breast carcinoma) and cancer (Swanson et al, 2014;Singh et al, 2017). In the latter category, associations were found with non-Hodgkin lymphoma or multiple myeloma incidence (Hardell and Eriksson, 1999;McDuffie et al, 2001;Hardell et al, 2002;De Roos et al, 2003Eriksson et al, 2008;Schinasi and Leon, 2014;Mesnage et al, 2015b), although other reviews claimed no causal relationship between exposure to glyphosate and lymphohematopoietic cancers (Acquavella et al, 2016;Chang and Delzell, 2016;Williams et al, 2016a). Some of these findings have been questioned by Monsanto (Acquavella et al, 1999) and a recent cohort prospective epidemiology study carried out in the US on 57310 licensed pesticide applicators and 32347 spouses in Iowa or North Carolina States found no apparent correlation between glyphosate use and solid tumor or lymphoid malignancies, including non-Hodgkin lymphoma, except for increased risk of acute myeloid leukemia in case of high exposure (Andreotti et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 98%
“…A large team of researchers including 96 research professors from 22 countries worldwide (Portier et al, 2016) analyzed the data. Taking a contrary position were a set of six studies published in the journal Critical Reviews in Toxicology (Acquavella et al, 2016;Brusick et al, 2016;McClellan, 2016;Solomon, 2016;Williams et al, 2016a,b), sponsored by Monsanto and other members of the pesticide industry, as declared in the papers themselves. These reviews focused on the carcinogenicity, genotoxicity of glyphosate and exposures to it, but considered partly the same data and followed the same concept published in a previous risk assessment by the same lead author (Williams et al, 2000).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…4% of the wives showed detectable levels of glyphosate in their urine, always on the day of application, with a maximum value of 3 ppb of substance, while 12% of the children, always in the same conditions and on the same day, had detectable values of glyphosate in their urine, with a maximum concentration of 29 ppb. The scientists who carried out the study concluded that the levels of glyphosate found in the farmers and their families did not reach or exceed the reference doses that could be tolerated by law, but they nonetheless recommended minimizing exposure to the pesticides [59,60].…”
mentioning
confidence: 99%
“…In 2004, two studies related to the monitoring of the concentration of glyphosate present in the urine of some families of farmers after coming into contact with the herbicide, were published [59,60]. The families that were part of the research were initially chosen based on the list of farmers authorized to use the pesticide in South Carolina and Minnesota and focusing on some aspects, among them:…”
mentioning
confidence: 99%